The incidence of dental caries in indigent Filipino children with cleft lip and/or palate (CLAP) from the Noordhoff Craniofacial Foundation Philippines, Incorporated (NCFPI) - Ildefonso, Eula C.
One in every 500 children born in the Philippines is diagnosed with cleft lip and/or palate (CLAP). Dental anomalies which arise in relation to the defect along with restrictions in oral hygiene are considered to be predisposing factors to the development of dental caries. However, there are hardly any studies which focus on the needs and conditions of these patients. This study aims to provide an overview and statistical data on the incidence of dental caries in Filipino children which can be used by dental health care professionals (DHCPs) as a guide in imparting the necessary oral hygiene instructions to the parents and caregivers of the patient to lessen pre-surgical treatment in other cases of CLAP in the future.